Eficacia desinfectante del acido peracetico sobre mesas y en locales de laboratorio. I. Accion virucida - Barrera, M.=700 1 Tablada, L.M.; Gonzalez, M.
(En, Es)
Ilus., 7 ref.
Keywords: HERPESVIRUS BOVINO; ENTEROVIRUS; DESINFECCION; LABORATORIOS; CUBA; ACIDO PERACETICO; ACCION VIRUCIDA